Manajemen Peningkatan Mutu Berbasis Sekolah - Rizadiliyawati, Rizadiliyawati; Dahrani, Dahrani; Busra, Aminudin; Mudasir, Mudasir (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study explores the concept of School-Based Quality Improvement Management (SBQIM) as a strategic approach to enhancing educational quality in Indonesia. SBQIM emphasizes the active involvement of school principals, teachers, and the community in the planning, implementation, and evaluation of educational programs. The role of transformational leadership by school principals is crucial in fostering a collaborative environment, motivating teachers, and effectively managing resources. Teachers' participation in decision-making and professional development, as well as community engagement in supporting school policies, are key factors for the success of SBQIM. However, challenges such as resource disparities between urban and rural schools and the lack of managerial competencies among school leaders need to be addressed through affirmative policies and continuous training. The study also highlights the importance of technology integration and regular evaluations involving all stakeholders to improve the implementation of SBQIM. With the right strategies and commitment from all parties, SBQIM can significantly contribute to improving the quality of education in Indonesia.